2021
DOI: 10.1126/science.abf2974
|View full text |Cite
|
Sign up to set email alerts
|

Merging shuttle reactions and paired electrolysis for reversible vicinal dihalogenations

Abstract: Vicinal dibromides and dichlorides are important commodity chemicals and indispensable synthetic intermediates in modern chemistry that are traditionally synthesized using hazardous elemental chlorine and bromine. Meanwhile, the environmental persistence of halogenated pollutants necessitates improved approaches to accelerate their remediation. Here, we introduce an electrochemically assisted shuttle (e-shuttle) paradigm for the facile and scalable interconversion of alkenes and vicinal dihalides, a class of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 80 publications
1
119
0
20
Order By: Relevance
“… 238 246 After that, only a few examples of electrosyntheses have been published, wherein both electrodes are required for the same process. 1 , 247 , 248 Hartmer and Waldvogel developed a domino oxidation–reduction sequence for the conversion of aldoximes to nitriles, where the first redox process is carried out on graphite anode and lead cathode is used in the second to generate the final compounds ( Scheme 18 ). 248 In this case, they utilized MTES, which is known from previous reports to protect the lead cathode from corrosion.…”
Section: Examples In Reductive Electroorganic Synthesismentioning
confidence: 99%
“… 238 246 After that, only a few examples of electrosyntheses have been published, wherein both electrodes are required for the same process. 1 , 247 , 248 Hartmer and Waldvogel developed a domino oxidation–reduction sequence for the conversion of aldoximes to nitriles, where the first redox process is carried out on graphite anode and lead cathode is used in the second to generate the final compounds ( Scheme 18 ). 248 In this case, they utilized MTES, which is known from previous reports to protect the lead cathode from corrosion.…”
Section: Examples In Reductive Electroorganic Synthesismentioning
confidence: 99%
“…= 90.5/9.5, 6b mono ) could be achieved with 5-bromopyridin-2-ol ligand. The absolute configuration of 6a mono after removal of the directing group was determined by x-ray crystallography (7). However, higher diastereoselectivity could not be obtained at present even after extensive study and further investigation is required.…”
Section: C-h Arylation Only Via C-c Rementioning
confidence: 99%
“…This approach is thus not directly transposable to catalytically shuttle two functional groups at once. Importantly, together with the Waldvogel group, Morandi and co‐workers showed that dissociative electron transfer pathways can be used to overcome bottlenecks in conventional shuttle catalysis schemes [25] . In constant current electrolysis conditions, 1,2‐dichloro species were reductively cleaved to mono‐chlorinated radicals, that readily expel chloride after further reduction.…”
Section: Cleaving Bonds With Electronsmentioning
confidence: 99%
“… Development of an e‐shuttle catalytic scheme (two functional groups shuttling) to overcome limitations of current (hydro)functionalization shuttle catalysis [25] …”
Section: Cleaving Bonds With Electronsmentioning
confidence: 99%